# algebra

I need a step by step explanation on how to add these two equations

2x+3y=1
5x+3y=16

Subtract the first equation from the second. (Subtract left and right sides separately). This gives you
3x = 15
Then divide both sides by 3.
x = 5
Pretty easy, huh?
After you have x, you can get y by using any of the original equations.
10 + 3y = 1
Subtract 10 from both sides.
3y = -9
Divide both sides by 3
y = -3

2x + 3y =1
5x + 3y = 16

Multiply the 2nd equation by -1, then add them together like this:

2x + 3y = 1
-5x - 3y =-16
_________________

-3x = -15

Divide by -3 to get x =5. Now, substitute 5 for x in one of the equations and solve for y.

1. 👍 0
2. 👎 0
3. 👁 124

## Similar Questions

1. ### Algebra 2

I need to know how to solve quadratic equations by factoring. Can you so a step by step explanation to this sample problem? 2 x -12x-28

asked by Joanna on November 30, 2009
2. ### algebra 1

ELEMENTARY ALGEBRA #3 Page 23 Chapter 3 Lesson 3.02 Solving Multi-step Equations Reading Assignment: Study pages 126 – 129 Written Assignment: There are five steps to solve Multi-Step equations, Match them in their proper order.

asked by Kyle on March 9, 2009
3. ### math

Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

asked by Anonymous on October 25, 2018
4. ### math,algebra II

I need someone to explain to me step by step the process of this problem its in my book as an example but i am not understanding it. Ive researched the explanation of the ECHELON METHOD...BUt i am not seeingit...this is the

asked by alma20 on June 1, 2007
5. ### Math

I am really have a tough time trying to solve this problem. I think my first three steps are correct but I am not sure. Could someone please help me? I got lost somewhere on one of these steps. I thonk it was step 3, 4, 5. Thank

asked by Tiffany on February 10, 2011
6. ### math

Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

asked by Valerie on October 22, 2019
7. ### Algebra1

I am solving for linear equations and I'm wondering if I did Step 3 right.. 3x-y=8 x-y=8 Step 1 3x-y=8 3x-y+y=8+y 3x=8+y 3x/3=8+y/3 x=(8+y/3) Step 2 3(8+y/3)-y=8 8+y-y=8 8+2y=8 8+2y-8=8-8 2y=0 2y/2=0/2 y=0 Step 3 x=8+y(0)/3 x=2.6

asked by Samantha on April 18, 2010

Can anybody tell me step wise step how to solve this quadratic equation? x^3-3x^2+4=0 Please tell me step wise step as i haven't solved such type of equations before. Thank You

asked by Akash on April 14, 2011
9. ### ALGEBRA HELP

When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

asked by cv on October 21, 2013
10. ### Precalculus

This is for solving exponential/logarithmic functions: (This is a base e Logarithmic function I would assume): e^(4x)/10 =4^x-2 ? I understand the properties of logs for the most part, but I have a hard time figuring out the

asked by Sarah on December 11, 2012

More Similar Questions